Overview of Hackathons in Brazil - Rodrigues, Renato Tadeu; Guimarães, Márcia Regina Neves; Lara, Felipe Ferreira de (Revista Gestão da Produção Operações e Sistemas, 2022)
Purpose – The main purpose of this study is to analyze why Brazilian organizations hold Hackathons and to identify what happens to the winning products after the event. Theoretical Framework – The open innovation practices promoted by Brazilian companies known as Hackathons, have become popular since 2014. The study has contributed to advances in holding Hackathons in Brazil, contributing to the spread of open innovation in Brazilian companies. Design/Methodology/Approach – Exploratory and qualitative research was used a study based on in-depth interviews to achieve its objectives. Interviews were conducted with six companies that promoted Hackathon events, three consultancies who organize Hackathons and twenty individuals who have participated. Findings – It was found that the events brought benefits, such as improving the organization’s image namely to the company itself and its stakeholders; supporting the development of an organizational culture focused on innovation and the retention of new creative employees. Research, Practical & Social Implications – Participants identified networking with other companies and other Hackathon agents as advantages, along with an exchange of skills and the possibility of contributing to social causes. Originality/Value – It was identified, in the study, that a hackathon is used by private companies to retain specialist labor, where the company sees it as an opportunity to find out, in practice, the behavior and knowledge of potential employees. A hackathon can also be held so that companies can test and validate their products or understand their problems in more detail, as many external participants may be or have been clients of the company promoting the event. Keywords – innovation, open innovation, hackathon.